Influence of Kunjal Kriya on Respiratory Physiology - A Comprehensive Review (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The ancient yogic cleaning technique known as Kunjal Kriya has garnered attention for its potential benefits to respiratory health. This comprehensive review examines Kunjal Kriya's physiological effects, focusing on its ability to enhance lung function, facilitate mucous clearance, and promote overall respiratory wellness. By integrating clinical evidence, current research findings, and traditional practices, this review aims to offer an in-depth understanding of Kunjal Kriya’s impact on respiratory health. The review begins with an exploration of Kunjal Kriya's historical origins and its relation to other yogic practices. It then delves into the physiological mechanisms through which Kunjal Kriya influences respiratory health, including the strengthening of respiratory muscles, increased oxygen intake, and enhanced lung capacity. These benefits are thought to improve tissue oxygenation and respiratory efficiency, potentially aiding those with respiratory conditions. Additionally, Kunjal Kriya’s role in facilitating mucus clearance from the respiratory system is highlighted. By inducing the gag reflex and promoting the expulsion of mucus from the throat and upper airway, Kunjal Kriya contributes to better respiratory hygiene and reduced incidence of infections, which is crucial for conditions characterized by mucus buildup. Beyond its physiological benefits, Kunjal Kriya supports general respiratory wellness through its emphasis on deep breathing and focused awareness. These elements foster mind-body integration, relaxation, and stress reduction, which may enhance overall respiratory health and complement conventional treatments. The review also discusses clinical evidence supporting Kunjal Kriya’s efficacy in respiratory management. While some studies show promising results, further research, including randomized controlled trials, is needed to validate and explore Kunjal Kriya’s potential as an adjunct therapy for various respiratory conditions. In conclusion, Kunjal Kriya offers a holistic approach to respiratory health by promoting overall wellbeing, facilitating mucous clearance, and improving physiological function. Further exploration of Kunjal Kriya’s effects could provide valuable insights into its role in respiratory health management.